Entrepreneurship Education: Encouraging Future Innovation Among Women In Ondo State, Nigeria - OMONIYI, ADESOJI OLUBUNMI (Advances in Social Sciences Research Journal, 2017)
Due to fast changes in the world economy and increase in the rate of unemployment globally especially in the last one and half decades of 21st century, there is the need for emergence of new kinds of business and jobs in order to meet up with the challenges of youth unemployment in general and women in particular. This paper gives an overview of how to get started in entrepreneurship education and its benefits to the development of the national economy vis-à-vis its sustaining innovation in providing jobs for the teaming population of unemployed youths. Emphasis are laid upon how small business entrepreneurship could be developed to large company entrepreneurship offering new products and making the entrepreneur function as the employer or boss rather than mere employees. Also, the paper stresses how women could be given the awareness of the social benefits they need to enjoy by giving them priorities and being considered eligible when receiving supplementary support because of their business acumen and naturally endowed managerial qualities. Ways of increasing the confidence level of women to take risk in setting up businesses are emphasized. The paper proposes a new action plan for government so that Nigerian women do not lag behind in the campaign for wealth creation through entrepreneurship opportunities in education. Benefits of entrepreneurship education are also stressed which include among others: job readiness, money management, improved health status, increases problem solving and decision making abilities for improved economic growth. Keywords: entrepreneurship, world economy, unemployment, innovations, wealth creation, economic growth